2011
DOI: 10.5120/2015-1833
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Location of FACTS Devices for Congestion Management in Deregulated Power Systems

Abstract: In the emerging deregulated electric power market, congestion management becomes extremely important and it can impose barrier to electric power trading. There are t w o types of congestion management methodologies to relieve congestion in transmission lines. One is non-cost free methods and another is cost-free methods, among them later method relieves the congestion technically whereas the former is related more with the economics. In this paper congestion is relieved using cost free method. Among the variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Literature [27] discussed an improved performance by using FACTS devices and optimal location of TCSC and UPFC for congestion management. In this paper, author implemented a nonlinear objective function which can be solved by genetic algorithm for optimal generation schedule for social welfare maximizing.…”
Section: Optimization Methodsmentioning
confidence: 99%
“…Literature [27] discussed an improved performance by using FACTS devices and optimal location of TCSC and UPFC for congestion management. In this paper, author implemented a nonlinear objective function which can be solved by genetic algorithm for optimal generation schedule for social welfare maximizing.…”
Section: Optimization Methodsmentioning
confidence: 99%
“…Whereas the combination of both series and shunt devices like UPFC allows for continuous control of all these factors. Some work has been done by the authors to reduce congestion by employing UPFC [29][30][31]. From the literature [24][25][26][27][28][29][30][31], which utilized different FACTS devices, it is observed that the UPFC FACTS device plays a vital role in controlling congestion.…”
Section: Introductionmentioning
confidence: 99%
“…The successive linear programming for solution of the security constraints economic dispatch is proposed in [11]. In [12] Optimal location of UPFC and TCSC is proposed to relieve the congestion in power system network. The genetic algorithm in conjunction with fuzzy logic is used to find the location of FACTS devices in power system as discussed in [13].…”
Section: Introductionmentioning
confidence: 99%